2000
DOI: 10.1046/j.1365-2133.2000.03298.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of fragrance allergy in a patch-test population over a 17-year period

Abstract: Fragrances are widely encountered in our daily environment and are known to be a common cause of allergic contact dermatitis. We have reviewed our patch test data from 1980 to 1996 to establish whether the pattern of fragrance allergy has changed with time. During this period, 25,545 patients (10,450 male, 15,005 female) were patch tested with the European standard series. The mean annual frequency of positive reactions to the fragrance mix was 8.5% in females (range 6.1-10.9) and 6.7% in males (range 5.1-12.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 21 publications
9
100
2
1
Order By: Relevance
“…These figures are in line with a previous study from Denmark (1,25), however, lower than reported in out-patient clinic studies (18,28). Moreover, there does not seem to be a concomitant positive patch test to balsam of Peru in fragrance-sensitive patients, which suggests that balsam of Peru is not a reliable marker of fragrance allergy (27).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These figures are in line with a previous study from Denmark (1,25), however, lower than reported in out-patient clinic studies (18,28). Moreover, there does not seem to be a concomitant positive patch test to balsam of Peru in fragrance-sensitive patients, which suggests that balsam of Peru is not a reliable marker of fragrance allergy (27).…”
Section: Discussionsupporting
confidence: 62%
“…The target group of the cosmetic industry has been women, but men, and more recently children, are the new and growing consumer groups. It is therefore to be expected that fragrance allergy will be an increasing health problem in these groups (26,27). Few reactions were found to colophony and balsam of Peru.…”
Section: Discussionmentioning
confidence: 99%
“…Reassuringly, there does not appear to have been any increase in eugenol hypersensitivity over the past two decades. 25 Furthermore, the oral implication of epi-cutaneous patch testing of dental materials is unclear. In general, the mouth and the oral mucosa appear to be less sensitive to contact allergens than the skin, possibly because allergens are constantly diluted and washed away by the saliva.…”
Section: Discussionmentioning
confidence: 99%
“…If patch test was used to investigate patients suspected of developing contact dermatitis, approximately 42∼54% would demonstrate positive reaction 1,6,18 . The reason behind such a high positive rate is that fragrances are included not only in the perfume but also in the various types of cosmetic product, detergent, medical product and others [19][20][21][22] . In this study, more than half of the tested products contained fragrance, which were confirmed to be included in various cosmetic product types other than the aroma products.…”
Section: Discussionmentioning
confidence: 99%